Revelation, Truth, Science. A Dispute Over the Relationship Between Philosophy and Theology in Czech Interwar Thought - Bęben, Dariusz (Folia Philosophica, 2023)
The aim of the article is to present the dispute regarding the relationship between philosophy and theology in Czech interwar thought (Kozák, Souček, Rádl, Patočka). The author discusses various ways of justifying theology and Revelation and their relations to philosophy. In this dispute, on the one hand, theologians try to justify the uniqueness of theology and also demonstrate its scientific nature. On the other hand, philosophers show that theology that is based on Revelation cannot be part of knowledge. The history of the dispute has shown that theology must maintain a distance from philosophy if it does not want to renounce its essence, its securitatis, which gives meaning to the existence of theology, and, which does not mean that it is insensitive to everyday human problems.